The formation of Slavic somatisms within the linguistic theory of O. Potebnya - Шпітько, Ірина Миколаївна; Жарко, Світлана Юріївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
Somatisms as the oldest lexical units that function in all modern Slavic languages and have deep roots are considered derivative nominations, which in their ontogenesis are figurative names as they depict the ancient Slavs` knowledge about the surrounding world, their ideas about themselves and their own organism in general. The research of somatisms is done on the basis of the nomination theory that was well-grounded by a Ukrainian linguist O. Potebnya, which is in studying the correlation of the surrounding world, thinking and language; various means of nomination; nomination technique; the process of the transformation of extralingual reality facts into the acquisition of the language system and structure. Somatisms belong to the oldest layer of lexicon in all Slavic languages, that`s why defining their nature and the mechanisms of their naming will make it possible to understand deeper the processes of nomination in these languages. The relevance of the research is explained by the fact that somatisms are the objects of a complex onomasiological and cognitive analysis that is aimed at revealing the processes of formation and nomination of parts of the boy in related Slavic languages and defining their derivatives. Somatisms were formed as a result of people`s acquaintance with properties of objects, thus, the ideas about these objects were formed. The image of the objects reproduced in our ancestors` consciousness or created by their imagination in the process of thinking and life activity generated the names of the parts of the body. Nomination of somatisms is mainly connected with procedural features, which perhaps were the most emotional or the most urgent for the object. That is why motivating for nominations „face”, „mouth”, „lips”, „eye”, „tooth” served old verb lexemes. During a prolonged use, the somatisms in different Slavic languages lost their semantic connection with the initial meaning-forming features and gained the status of „image free” nominations.